Sains Islam Dalam Perspektif Filsuf Modern - Andi Huzaifa; Nurul Adawia; Ramsiah Tasruddin (Yayasan Al-Afif, 2025)
This article examines the concept of Islamic science from the perspective of modern Muslim philosophers and scholars, with a particular focus on its epistemological foundations. The study departs from the problem of the dichotomy between science and religion that has developed within the tradition of modern Western science, as well as from contemporary Islamic intellectual efforts to formulate a scientific paradigm grounded in revelation, reason, and empirical experience. Employing a qualitative approach with a library research design, this study conducts a conceptual analysis of philosophical works and contemporary writings on Islamic science. The findings indicate that the epistemology of Islamic science does not reject scientific methods; rather, it situates them within an integrative and ethically grounded Islamic worldview. Accordingly, Islamic science offers a holistic alternative paradigm for addressing the fragmentation of knowledge and the erosion of values in modern science.